A needs analysis on English language curriculum for community colleges / Zuliana Zulkiflee Chandra - Zulkiflee Chandra, Zuliana (2008)
The Malaysian government has taken the decision to use English as a medium of instruction for the teaching of Mathematics and Science subjects in schools beginning 2002. Due to the change in the language policy the Community Colleges (CC) are also involved in implementing the teaching of Mathematics, Science and technical subjects in English. To meet these needs, the CC adopts the English for Communication (EFC) modules for Semester 1 and Semester 2 students. After its implementation, it is timely to review the EFC modules at CC by carrying out a needs analysis. This study investigates the students and English lecturers’ opinion towards the effectiveness of the current English for Communication (EFC) modules. It also attempts to identify if there is a need to have specific English for the Community Colleges. Two sets of questionnaires were constructed and used for the purpose of this study. Five English Language lecturers and 90 Semester Four students at Kuala Langat Community College participated in this preliminary study. The findings from the study indicate that English and the four skills are important to the students with speaking and writing indicated as the most important. The study also indicated that the majority of students agreed that the EFC modules have helped them to understand the Mathematics, Science and technical subjects besides helping them to prepare for the job market. However, the lecturers indicated otherwise. They stated that the EFC modules have not helped the students to understand the Mathematics, Science and technical subjects and have not helped them to prepare for the job market. Findings also suggest improvement and changes should be made in accordance with the data gathered from the study. Among them are the content of the modules should be based on the students’ field of study and the syllabus should be tailored to the students’ needs. The study also shows that the lecturers indicated there is a need for a specific type of English. English for Specific Purposes (ESP) was chosen as the most suitable type of English for the Community Colleges. As this study was carried out on one group of students and English lecturers from one community college, that is, the Kuala Langat Community College (KLCC), it is recommended that a more comprehensive study be done involving all community colleges in Malaysia.